Efforts To Improve Writing Ability Through The Mind Mapping Learning Method - Wahyuningsih, Eka Prasetya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to describe the improvement of the writing learning process through the Mind Mapping learning method by enhancing the learning process of the Indonesian language subject. The research was conducted using the Classroom Action Research (PTK) method. The subjects of this study were the researcher as the classroom action performer and the fifth-grade students of SDN 02 Gawanan. The data collection method used in this study included student test results and observation sheets. The research procedure consisted of 2 cycles, each including planning, implementation, observation, and reflection. This research can be used to determine students' activity and problem-solving approach in the learning process. From the research results, it can be seen that the application of the Mind Mapping method was effective in planning, leading to an improvement in report writing skills for the second semester fifth-grade students of SDN 02 Gawanan. This is evidenced by the average test scores increasing to 72.62 with a learning mastery rate of 61.5% in the first cycle and 76.23 with a learning mastery rate of 84.6% in the second cycle. This improvement met the Minimum Criteria of Mastery and the predetermined learning mastery standard. The conclusion of this research is that students' abilities can be enhanced through the Mind Mapping learning method.